Understanding human navigation using network analysis - Iyengar, Sudarshan; Veni Madhavan, C. E.; Zweig, Katharina A.; Natarajan, Abhiram (Topics in cognitive science, 2012)
We have considered a simple word game called the word-morph. After making our participants play a stipulated number of word-morph games, we have analyzed the experimental data. We have given a detailed analysis of the learning involved in solving this word game. We propose that people are inclined to learn landmarks when they are asked to navigate from a source to a destination. We note that these landmarks are nodes that have high closeness-centrality ranking.
Gesehen am 21.11.2018